1996
DOI: 10.1164/ajrccm.154.1.8680681
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory events in the blood and airways of guinea pigs immunized to toluene diisocyanate.

Abstract: Toluene diisocyanate (TDI)-induced asthma is a common cause of occupational lung disease. We used a model to investigate the course of bronchopulmonary inflammation following immunization with TDI. Guinea pigs were immunized by weekly intradermal injections and challenged with TDI 7 d after the third injection. The animals were killed at different times after challenge and prepared for histologic examination of central and peripheral airways, for immunohistochemical studies of T lymphocyte and eosinophil distr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 29 publications
1
10
0
1
Order By: Relevance
“…Mast cells [19], activated T cells, and levels of neutrophilic infiltration [20] are also increased in TDI-OA as compared with AEC and AA. These results have been replicated in animal models of TDI-OA [21,22]. Although Bentley et al [23] reported that activated T cells and eosinophils were Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Mast cells [19], activated T cells, and levels of neutrophilic infiltration [20] are also increased in TDI-OA as compared with AEC and AA. These results have been replicated in animal models of TDI-OA [21,22]. Although Bentley et al [23] reported that activated T cells and eosinophils were Fig.…”
Section: Discussionmentioning
confidence: 76%
“…Hierzu liegen zahlreiche -auch mechanistische -Untersuchungen an Kaninchen und Meerschweinchen sowie in vitro vor, auf die hier nicht näher eingegangen wird. Auf eine Übersichtsarbeit (Raulf-Heimsoth und Baur 1998) und einige neuere Untersuchungen hierzu (Gagniere et al 1996(Gagniere et al , 1997Lastbom et al 1996;Mapp et al 1996;Marek et al 1996) sei verwiesen.…”
Section: Hautunclassified
“…They received 3 weekly intradermal injections of 50 yl of 100% TDI (2,4 and 2,6 isomers, ratio 80: 20) or saline into each of 2 dorsal sites (16). The injection of 100 yl of TDI was selected because this dose was able to induce both antibody production (17) and pulmonary sensitization in guinea pigs (16). Seven days after the 3rd injection of TDI, 5 animals of the group of immunized (N=10) and 5 of the group of nonimmunized animals (N=10) were challenged with TDI in a glass chamber (30 1).…”
Section: Immunization and Challenge By Toluene Diisocyanatementioning
confidence: 99%
“…Seven days after the 3rd injection of TDI, 5 animals of the group of immunized (N=10) and 5 of the group of nonimmunized animals (N=10) were challenged with TDI in a glass chamber (30 1). The challenge was done as previously described (16). All the immunized guinea pigs showed local irritation at the sites of the 2nd and 3rd injection of TDI.…”
Section: Immunization and Challenge By Toluene Diisocyanatementioning
confidence: 99%
See 1 more Smart Citation